The Effectiveness of Interactive Educational Technology in Teaching Complex Sentences: A Lesson Learned from Remote EFL Learners - Hadi, M. Wahyu; Masyudi, Masyudi; Yulandari, Evi Safitri (Journal of Language and Literature Studies, 2024)
EFL learners often encounter difficulties in mastering complex sentences, especially when they are treated by using conventional teaching methods. This study investigates the effectiveness of interactive educational technology in improving the EFL learners’ grammatical competences of complex sentences at the Institute of Global Nusantara Education. An experimental design was employed in this study. The samples of the study are all students who took Grammatical course at English language education study programe at the Institute of Global Nusantara Education. The research instruments comprise grammatical tests to see EFL learners’ grammatical competence. The tests are done in the experimental and control groups. Based on the data analysis, the findings demonstrate that the experimental group outperformed the control group, with significantly higher post-test scores (M = 85.6, SD = 5.2) compared to the control group (M = 72.3, SD = 4.8), an F-value of 65.14, and a p-value of 0.021. These results highlight the efficacy of interactive educational technology in not only enhancing students’ grammatical competences in writing activities but also boosting their motivation and engagement. Furthermore, these findings have broad implications for diverse educational settings, suggesting that integrating such technology can help bridge learning gaps, especially in contexts with varied access to resources. By addressing these challenges, educators can foster equitable and effective learning environments that support the development of advanced language skills.